The holographic supersymmetric Casimir energy - Benetti Genolini, P; Cassani, D; Martelli, D; Sparks, J (American Physical Society, 2017)
We consider a general class of asymptotically locally AdS5 solutions of minimal gauged supergravity, that are dual to superconformal field theories on curved backgrounds S 1 × M3 preserving two supercharges. We demonstrate that standard holographic renormalization corresponds to a scheme that breaks supersymmetry. We propose new boundary terms that restore supersymmetry, and show that for smooth solutions with topology S 1 ×R 4 the improved on-shell action reproduces both the supersymmetric Casimir energy and the field theory BPS relation between charges.